The peculiarities' study of higher education applicants' employment in pharmaceutical specialties of full-time training - A. A. Kotvitska; D. Yu. Tarasenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2017)
Employment of applicants of pharmaceutical higher education has both positive and negative impact on the quality of educational services provided by institutions, especially in terms of knowledge and skills acquired by student.